Density dependence and persistence of Morogoro arenavirus transmission in a fluctuating population of its reservoir host. Issue 2 (6th October 2019) - Mariën, Joachim; Borremans, Benny; Verhaeren, Christophe; Kirkpatrick, Lucinda; Gryseels, Sophie; Goüy de Bellocq, Joëlle; Günther, Stephan; Sabuni, Christopher A.; Massawe, Apia W.; Reijniers, Jonas; Leirs, Herwig
Abstract: A key aim in wildlife disease ecology is to understand how host and parasite characteristics influence parasite transmission and persistence. Variation in host population density can have strong impacts on transmission and outbreaks, and theory predicts particular transmission–density patterns depending on how parasites are transmitted between individuals. Here, we present the results of a study on the dynamics of Morogoro arenavirus in a population of multimammate mice ( Mastomys natalensis ). This widespread African rodent, which is also the reservoir host of Lassa arenavirus in West Africa, is known for its strong seasonal density fluctuations driven by food availability. We investigated to what degree virus transmission changes with host population density and how the virus might be able to persist during periods of low host density. A seven‐year capture–mark–recapture study was conducted in Tanzania where rodents were trapped monthly and screened for the presence of antibodies against Morogoro virus. Observed seasonal seroprevalence patterns were compared with those generated by mathematical transmission models to test different hypotheses regarding the degree of density dependence and the role of chronically infected individuals. We observed that Morogoro virus seroprevalence correlates positively with host density with a lag of 1–4 months. Model results suggest that the observed seasonal seroprevalence dynamics can be best explained by a combination of vertical and horizontal transmission and that a small number of animals need to be infected chronically to ensure viral persistence. Transmission dynamics and viral persistence were best explained by the existence of both acutely and chronically infected individuals and by seasonally changing transmission rates. Due to the presence of chronically infected rodents, rodent control is unlikely to be a feasible approach for eliminating arenaviruses such as Lassa virus from Mastomys populations. Abstract : This study addresses key concepts in disease ecology (density‐dependence of transmission, juvenile dilution effects on seroprevalence, and pathogen persistence in a fluctuating host population) using a long‐term dataset of a natural host population and finds compelling support for an expected (but rarely found) effect of population density on transmission.